Snow induced collapse of hail protection canopies. (September 2017) - Vatansever, Cüneyt; Seçkin, Edip; Yazıcı, Gökhan
Abstract: This paper addresses the snow induced collapse of hail protection canopies of a major car dealership in Istanbul, Turkey. Each of them with different plan dimensions has been built to provide an enclosed space of over 50, 000 square meters for parking. The structural system of each hail protection canopy consists of successive steel frames spaced at 5.0 m intervals. Some of these canopies collapsed on January 1st, 2016. The rest has been saved thanks to the immediate intervention provided by the employees allowing accumulated snow to slide off the roof. Following the incident, a site investigation has been conducted to inspect the structural failures and a numerical 3D model to represent the whole structure was developed using OpenSEES to understand the collapse mechanism of the hail protection canopies. In addition, the scope of the structural design calculations was examined to check for potential incorrect design assumptions. Consequently, site observations and analysis results indicate that the hail protection canopies collapsed due to a combination of erroneous design assumptions on snow load and the poor design and construction of structural members and their connections. Highlights: The inspection made in site was presented and observations were assessed. Bolted end plate connection behavior was developed based on yield line theory. Numerical model of structural system was also prepared to perform nonlinear analysis. Structural system collapsed as a consequence of wrong assumptions on snow loading. Collapse mechanism was mostly controlled by the behavior of the connections.